Beproefde gevels (Bulletin KNOB, 2007)
The patron saint of the bricklayers' guild varied from town to town: St Barbara occurs regularly, but also the Four crowned ones (Antwerp and Dordrecht) and even St Joseph in case there was cooperation with the carpenters (Leiden). Throughout the Netherlands the history of these guilds dates back to the Middle Ages, but the oldest written regulations concerning the masterpiece were not drawn up until around the '40s of the 16th century.Usually this period is not considered to be the Middle Ages anymore, because by that time the Renaissance dawned in the Low Countries. The new form language and a different procedure - with craftsmen attracted from elsewhere - may have to do with the fact that regulations were tightened up. Making citizenship and payments obligatory was a primary point, besides marking off the trade as compared to related trades and in particular the necessity to make various test pieces.Sometimes it is not clear whether this concerned entry into the guild as a craftsman or obtaining the master's title, whereby it is sometimes stated that only this latter, highest level could entail the training of apprentices. The earliest description of the masterpiece is to be found in Haarlem in 1542. In the second half of the 16'h century most South-Holland towns followed, of which the regulations and the number of tests - usually four - can be compared with each other and, in fact also with those of the town of Antwerp.As regards the place of execution a distinction is apparent between towns such as Amsterdam (ill. 10), Delft, Amersfoort and Leeuwarden, where the masterpieces were brought together in one single building, and towns such as Haarlem, Dordrecht and Leiden, where they were to be seen throughout the town, both for the benefit of private individuals and in order to contribute to the beauty of the town in general.In Dordrecht this is explicitly stated. A town regulation from 1727 simultaneously saw to it that these masterpieces could no longer be erected on the main streets, but only on back streets. This measure was not intended to cheer up the poor districts with beautifully executed masonry from now on. The test facades displayed an unchanging traditionalism, whereas practice and fashion meanwhile prescribed quite different (taut) forms, which automatically appeared in the well-to-do main streets.Actually, this is a modernist building regulation regarding external appearance. In the 17th century the wooden façades had been successfully banished from the streetscape, not so much because of the fire risk, but because they were considered disfigurements of the townscape and were out of fashion. In the eyes of the guild stepped gables with basket arches and corbelling, just as ingeniously built brick vaults, represented the highest degree of workmanship.Since Romanticism and the advent of preservation of monuments in the second half of the 19th century, gable ends and ornamental brickwork were highly appreciated, but previously good taste had prescribed quite different forms for about a century and a half. In 1727 the Dordrecht town council relegated stepped gables and basket arches to the back streets; later in that century they demanded that façades be exclusively built on the building line, not with inclined elevations or fitted with canopies.